2004
DOI: 10.1161/01.res.0000129579.59664.9d
|View full text |Cite
|
Sign up to set email alerts
|

Increased Vulnerability to Atrial Fibrillation in Transgenic Mice With Selective Atrial Fibrosis Caused by Overexpression of TGF-β1

Abstract: Abstract-Studies on patients and large animal models suggest the importance of atrial fibrosis in the development of atrial fibrillation (AF). To investigate whether increased fibrosis is sufficient to produce a substrate for AF, we have studied cardiac electrophysiology (EP) and inducibility of atrial arrhythmias in MHC-TGFcys 33 ser transgenic mice (Tx), which have increased fibrosis in the atrium but not in the ventricles. In anesthetized mice, wild-type (Wt) and Tx did not show significant differences in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
400
0
11

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 496 publications
(426 citation statements)
references
References 40 publications
15
400
0
11
Order By: Relevance
“…TGF has been shown to be critical in cardiac fibrosis in various experimental models (Lijnen et al, 2000), and inhibition of TGF in such models prevents fibrosis (Teekakirikul et al, 2010). Myocardial overexpression of TGF1 induces atrial, but not ventricular fibrosis (Nakajima et al, 2000;Verheule et al, 2004). Possibly, this remarkable difference in fibrotic response between atria and ventricles is caused by the abundance of CCN2 in atria, which may enhance the effects of TGF (Daniels et al, 2009).…”
Section: Effect Of Profibrotic Stimuli On Cfmentioning
confidence: 99%
“…TGF has been shown to be critical in cardiac fibrosis in various experimental models (Lijnen et al, 2000), and inhibition of TGF in such models prevents fibrosis (Teekakirikul et al, 2010). Myocardial overexpression of TGF1 induces atrial, but not ventricular fibrosis (Nakajima et al, 2000;Verheule et al, 2004). Possibly, this remarkable difference in fibrotic response between atria and ventricles is caused by the abundance of CCN2 in atria, which may enhance the effects of TGF (Daniels et al, 2009).…”
Section: Effect Of Profibrotic Stimuli On Cfmentioning
confidence: 99%
“…Nevertheless, it has been reported that the mouse atria are able to sustain fibrillation 14,17,25,26 . Thus, despite the small sizes of mouse atria, our knockout mouse allowed for the investigation of the mechanisms underlying the genesis and maintenance of AF.…”
Section: Study Limitationsmentioning
confidence: 99%
“…13,14 Finally, a recent transgenic mouse model demonstrated that in the presence of atrial fibrosis, even very small atria can fibrillate. 15 Although fibroblasts are generally considered to be classic examples of nonexcitable cells, in cultured monolayers, some are able to generate and propagate action potentials. These action potentials are based on activation of L-type calcium channels and propagate very slowly (Ͻ0.01 m/s).…”
Section: See P 394mentioning
confidence: 99%